2019
DOI: 10.7717/peerj.8163
|View full text |Cite
|
Sign up to set email alerts
|

Different distant metastasis patterns based on tumor size could be found in extensive-stage small cell lung cancer patients: a large, population-based SEER study

Abstract: Background Small-cell lung cancer (SCLC) is a malignant cancer with the ability to metastasize quickly. The relationship between tumor size and the distant metastasis patterns of Extensive-Stage Small Cell Lung Cancer (ES-SCLC) has not been reported.ObjectivesThe aim of this study was to determine the different distant metastasis patterns as they related to tumor size in ES-SCLC.Patients and MethodsWe used Surveillance, Epidemiology, and End Results (SEER) population-based data collected from 2010 through 2013… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 34 publications
6
13
0
Order By: Relevance
“…8 , 15 , 16 Notably, most of these studies were limited by institutional experiences or statewide databases and mainly focused on NSCLC and extensive-stage SCLC. 17 , 18 , 19 As a result, the validity of race, among other factors, for limited-stage (stages I-III) SCLC (L-SCLC) is not well understood. Unlike extensive-stage SCLC, which is incurable and primarily treated with systemic chemotherapy with or without immunotherapy, L-SCLC is potentially curable and treated primarily with concurrent chemoradiotherapy or surgery followed by adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…8 , 15 , 16 Notably, most of these studies were limited by institutional experiences or statewide databases and mainly focused on NSCLC and extensive-stage SCLC. 17 , 18 , 19 As a result, the validity of race, among other factors, for limited-stage (stages I-III) SCLC (L-SCLC) is not well understood. Unlike extensive-stage SCLC, which is incurable and primarily treated with systemic chemotherapy with or without immunotherapy, L-SCLC is potentially curable and treated primarily with concurrent chemoradiotherapy or surgery followed by adjuvant chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 10%-25.8% of patients with SCLC at diagnosis had symptomatic or asymptomatic brain metastases. [26][27][28][29][30] The effects of chemotherapy in patients with brain metastasis are limited, and whole brain radiotherapy is the current therapeutic model for SCLC with brain metastasis. Recently, a Phase II study reported the preliminary efficacy of pembrolizumab for patients with NSCLC with untreated brain metastases.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 20.3%-44.8% of SCLC patients presented with liver metastases at the time of diagnosis. 30,32,33 It has previously been reported that the one-year survival rate of SCLC patients with liver metastasis is less than 20%. 33 In the KEYNOTE-189 study (2019 AACR), pembrolizumab plus chemotherapy improved PFS and OS in nonsquamous NSCLC patients with liver metastases unlike chemotherapy alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations